Measuring the legacy of mega-events: sportive usage index of the Brazil 2014 FIFA World Cup™ - Rômulo Meira Reis; Lamartine Pereira DaCosta; Silvio de Cassio Costa Telles (Universidade Estadual Paulista (UNESP), 2021)
Abstract Aims: This study's general objective is to analyze the sportive usage of the 12 Brazil 2014 FIFA World Cup™ arenas. The specific objectives are: (i) To measure the 12 arenas' sportive legacy usage; (ii) To examine and analyze the causes and effects of the results that were found; and (iii) To develop a sportive usage index. Methods: To achieve these objectives, the documental research method was employed. Once in possession of the qualitative and quantitative data, parameters were established for the analysis, which was limited by the seasons from 2014 to 2019. We then constructed tables and applied statistical treatment. Results: 2014 Season: 215 matches; 2015 Season: 287 matches; 2016 Season: 248 matches; 2017 Season: 260 matches; 2018 Season: 296 matches; and 2019 Season: 325 matches. These results revealed extremes, with some arenas receiving little use and others being highly used. The sportive usage index was about ≅23 matches/year and 2 matches/month. Conclusions: These results are not random and occurred due to matters pertaining to Brazilian soccer peculiarities, with an emphasis on successive increases in the number of competitions; a large number of matches per year; arenas constructed in locations with low popularity teams that receive little use; and political and management issues that interrupted an arena's use (Maracanã in 2016) We recommend that new studies be conducted focusing on the management of these arenas, their state of maintenance and/or conservation, costs, budgets and the use of public resources in their construction.